Chemoreactive Nanotherapeutics by Metal Peroxide Based Nanomedicine. Issue 1 (3rd December 2020) - Hu, Hui; Yu, Luodan; Qian, Xiaoqin; Chen, Yu; Chen, Baoding; Li, Yuehua
Abstract: The advances of nanobiotechnology and nanomedicine enable the triggering of in situ chemical reactions in disease microenvironment for achieving disease‐specific nanotherapeutics with both intriguing therapeutic efficacy and mitigated side effects. Metal peroxide based nanoparticles, as one of the important but generally ignored categories of metal‐involved nanosystems, can function as the solid precursors to produce oxygen (O2 ) and hydrogen peroxide (H2 O2 ) through simple chemical reactions, both of which are the important chemical species for enhancing the therapeutic outcome of versatile modalities, accompanied with the unique bioactivity of metal ion based components. This progress report summarizes and discusses the most representative paradigms of metal peroxides in chemoreactive nanomedicine, including copper peroxide (CuO2 ), calcium peroxide (CaO2 ), magnesium peroxide (MgO2 ), zinc peroxide (ZnO2 ), barium peroxide (BaO2 ), and titanium peroxide (TiOx ) nanosystems. Their reactions and corresponding products have been broadly explored in versatile disease treatments, including catalytic nanotherapeutics, photodynamic therapy, radiation therapy, antibacterial infection, tissue regeneration, and some synergistically therapeutic applications. This progress report particularly focuses on the underlying reaction mechanisms on enhancing the therapeutic efficacy of these modalities, accompanied with the discussion on their biological effects and biosafety. The existing gap between fundamental research and clinical translation of these metal peroxide based nanotherapeutic technologies is finally discussed in depth. Abstract : This progress report summarizes and discusses the most representative paradigms of metal peroxides in chemoreactive nanomedicine, particularly focusing on the underlying reaction mechanisms on enhancing therapeutic efficacy in versatile diseases and discussing biological effects and biosafety. The existing gap between fundamental research and clinical translation of these metal peroxide based nanotherapeutic technologies is finally discussed in depth.